A meta-analysis of transcranial direct current stimulation for schizophrenia: "Is more better?". (March 2019) - Kim, Julia; Iwata, Yusuke; Plitman, Eric; Caravaggio, Fernando; Chung, Jun Ku; Shah, Parita; Blumberger, Daniel M.; Pollock, Bruce G.; Remington, Gary; Graff-Guerrero, Ariel; Gerretsen, Philip
Abstract: Transcranial direct current stimulation (tDCS) has generated interest in recent years as a potential adjunctive treatment for patients with schizophrenia. The primary objective of this meta-analysis was to evaluate the efficacy of tDCS on positive symptoms, particularly auditory hallucinations, and negative symptoms. A literature search of randomized sham-controlled trials was conducted using the OVID database on October 9, 2018. The standardized mean differences (SMDs) were calculated to examine changes in symptom severity between active and sham groups for the following symptom domains: auditory hallucinations, positive symptoms (including auditory hallucinations), and negative symptoms. Moderator analyses were performed to examine the effects of study design and participant demographics. We identified 10 eligible studies. Main-analyses showed no effects of tDCS on auditory hallucinations (7 studies, n = 242), positive symptoms (9 studies, n = 313), or negative symptoms (9 studies, n = 313). Subgroup analyses of studies that applied twice-daily stimulation showed a significant reduction in the severity of auditory hallucinations (4 studies, n = 138, SMD = 1.04, p  = 0.02). Studies that applied ≥10 stimulation sessions showed a reduction in both auditory hallucination (5 studies, n = 186, SMD = 0.86, p  = 0.009) and negative symptom severity (7 studies, n = 257, SMD = 0.41, p  = 0.04). Meta-regression analyses revealed a negative association between mean age and the SMDs for auditory hallucinations and negative symptoms, and a positive association between baseline negative symptom severity and the SMDs for negative symptoms. Our findings highlight the need to optimize tDCS parameters and suggest twice-daily or 10 or more stimulation sessions may be needed to improve clinical outcomes in patients with schizophrenia. Highlights: Our primary analyses showed no effects of tDCS on positive or negative symptoms. Twice-daily tDCS was associated with reduced severity of auditory hallucinations. More than 10 tDCS sessions was associated with reduced auditory hallucination and negative symptom severity. Effects of tDCS on symptom severity were negatively associated with age.